Financial Statement Analysis as a tool for performance evaluation: A Study of Oscar FX Pvt. Ltd - Pandurangarao, K.; Raju, P.V.M. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This research paper presents an in-depth and systematic analysis of the financial statements of Oscar FX Private Limited, a rapidly growing and reputed company in the Visual Effects (VFX) industry, headquartered in Hyderabad, India. As the global media and entertainment landscape becomes increasingly competitive and digitally driven, understanding the financial health of a company like Oscar FX is crucial for investors, stakeholders, and management to ensure sustainable growth and long-term viability. The primary objective of this study is to evaluate the financial performance, stability, and growth trajectory of the company over a three-year period (2021–2024). To achieve this, the research focuses on various financial parameters by utilizing key tools of financial statement analysis, including ratio analysis, trend analysis, and comparative analysis. These tools are applied to interpret data from the company’s balance sheets, income statements, and cash flow statements. The study systematically examines the firm’s liquidity position, profitability margins, solvency capabilities, and operational efficiency through specific ratios such as the current ratio, quick ratio, debt-equity ratio, return on equity (ROE), return on assets (ROA), and asset turnover ratios. The results show that while Oscar FX has demonstrated consistent growth in revenue and profits, there are significant concerns surrounding its liquidity and asset utilization efficiency. For instance, declining cash ratios and increasing debt levels may pose potential financial risks if not addressed strategically.